The Dark Triad traits in the South African workplace: moderators of career interests and success - Oldewage, Denise; Jonck, Petronella (Frontiers in Psychology, 2025)
IntroductionNumerous studies have been conducted on the nexus between the Dark Triad personality traits and the influence thereof within the context of work. However, a paucity of studies underscores the interaction between these traits with career interests and success, particularly within the South African context. This study aimed to investigate the direct and indirect effect of the Dark Triad traits on career interest and career success.MethodsA quantitative approach utilizing a cross-sectional design collected 406 responses from economically active participants using convenience sampling. The structured self- reported survey included the South African Career Interest Inventory (SACII-Short), The Dark Triad Dirty Dozen (DTDD) and the Subjective Career Success Inventory (SCSI). Structural equation modeling (SEM) and moderation analysis were performed to examine the data.ResultsPsychopathy had a statistically significant negative effect on both career interests and career success. Contrarily, narcissism did not have a statistically significant impact on either career interest or career success. Machiavellianism had a detrimental effect on career success but not career interest. The moderation analysis supported the hypothesis that psychopathy moderates the relationship between investigative career interest and career success negatively, underscoring the disruptive nature of this trait on career outcomes.DiscussionOrganizations should practice caution when hiring or promoting individuals with Dark Triad traits, particularly in positions requiring collaboration, trust and long-term success. This could be achieved by integrating personality assessments such as the DTDD into leadership development, talent development and HR policies interventions to reduce the negative consequences of the mentioned attributes to career success.